CURRENT SCENARIO OF ANTYODAYA PHILOSOPHY OF PANDIT DEENDAYAL UPADHYAYA - Singh, Durga Prasad; Singh, Azad Pratap (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Pandit Deendayal Upadhyaya was not just a politician, he was also a high class thinker, philosopher and writer. In this form, he had imagined a developed nation in a strong and balanced form. He had given up personal interests and comforts. He had no ambition in his personal life. He had dedicated his life to the society and the nation. This is what makes him great. Even after being continuously active in politics, he used to take out time for study and writing. For this, he used to cut down his rest time. In this, he also used to meet people and travel continuously. He liked to live among the common people. Perhaps this was the reason that he had understood the problems of the common man of the country very well. This subject was included in his thinking and study.